Characterization And Growth Kinetics Of Local N2-Fixing Bacterium, Bacillus Sp. Upmb10 - Ooi, Tze Chean (2002)
The production of locally isolated N2-fixing bacteria was undertaken in Fermentation Technology Unit, Enzyme and Microbial Technology Laboratory, Institute of Bioscience, Universiti Putra Malaysia. Cellular studies and biochemical tests conducted on Bacillus sp UPMB10 suggests that the bacterium is Bacillus sphaericus. Optimization of medium for cultivation of the N2-fixing Bacillus was achieved using 1.4 g/L of glycerol and 2.0 g/L of yeast extract. Addition of biotin and thiamine did not improve growth of the bacteria. Optimum culture condition for growth of UPMB10 in the 2L: stirred tank fermenter was obtained at initial pH range between pH 6.0-8.0, 30°C, at agitation speed of 600 rpm and airflow rate of 0.5 VVM. Viable cell counts obtained under these conditions were approximately 3.5 X 109 cfu/mL. A model employing the logistic equation was proposed to describe growth of this newly isolated Bacillus. The values of the general kinetic parameters were calculated from the analysis of experimental data obtained from a number of culture using batch fermentation. The specific growth rates of 0.40 h-1 and 0.45 h-1 were employed for modeling of bacteria growth in a shake flask and in 2 L fermenter, respectively. The proposed model consisting of general kinetic parameters and the specific growth rate was adequate to describe the fermentation data with sufficient accuracy for prediction of biomass production and substrate consumption. Due to substrate inhibition, production of the bacteria was further enhanced using an exponential fed-batch fermentation technique. With the specific growth rate maintained at 0.4 h-l, viable cells obtained using fed-batch fermentation was four times higher than batch cultivation of the bacteria. Cell density and productivity was improved by three fold compared to batch cultivation. In all experiments acetylene reduction assay (ARA) levels remained unchanged and was maintained at 20 nmol C2H2/hr/mL.